Approaches to Measuring the Stock of Human Capital A Review of Country Practices - Boarini, Romina (OECD Statistics Working Papers, 2012)
The paper reviews some national initiatives related to measuring the stock of human capital, indentifies some challenges to be addressed to improve the quality of existing monetary measures of human capital, and suggests developing experimental satellite accounts for education to better understand how human capital is produced and the linkages between education and its non-monetary outcomes